Academic career outcomes of Orthopedic Research and Education Foundation resident grant recipients. Issue 2 (1st June 2022) - Silvestre, Jason; Burgess, Regan K.; Nelson, Charles L.; Thompson, Terry L.
Abstract: The Orthopedic Research and Education Foundation (OREF) awards resident research grants to orthopedic surgery residents. Outcomes are lacking for OREF resident grant recipients including academic career choice and scholarly productivity. This was a retrospective cohort study of OREF resident grant recipients (2012–2020). The percentage of OREF resident grant recipients selecting an academic career was compared with the percentage of academic orthopedic surgeons in the United States via a χ 2 test. Two hundred and seventy‐six OREF resident grants were issued to 272 orthopedic surgery residents at 73 programs. OREF resident grant recipients were predominantly male (79.0%) and Caucasian (70.2%). OREF resident grant recipients had greater women representation than the national cohort of orthopedic surgery residents (21.0% vs. 16.0%, p  = 0.030) with similar proportions of underrepresented racial minorities (29.8% vs. 27.2%, p  = 0.351). OREF resident grants consisted of clinical (69.6%) and basic/translational science (30.4%) research and were awarded mostly for sports medicine (25.4%), trauma (18.8%), and adult reconstruction (15.9%) topics. The average h‐index was 8.5 ± 9.2 resulting from 29.5 ± 51.2 manuscripts. The majority of OREF resident grant recipients selected an academic career, which was higher than the national benchmark of academic orthopedic surgeons (63.8% vs. 24.4%, p  < 0.001). Two OREF resident grant recipients transitioned to National Institutes of Health research funding (0.7%). Multivariable logistical regression demonstrated two independent characteristics associated with pursuit of a future academic career: female sex ( p  = 0.042) and higher h‐index values ( p  = 0.002). Procurement of OREF resident grants is associated with pursuit of an academic career. Clinical significance: There is great interest in fostering the next generation of orthopedic surgeon scientists. Results from this study demonstrate the association between receipt of an OREF resident research grant and pursuit of a future career in academic orthopedic surgery.